Teacher-parent collaboration for an inclusive classroom: success for every child / Donnie Adams, Alma Harris and Michelle Suzette Jones - Adams, D.; Harris, A.; Jones, M.S. (University of Malaya, 2016)
This article outlines the findings from a contemporary study of teacher-parent collaboration in inclusive education in primary and secondary schools in Malaysia. Recent inclusive education policy developments within Malaysia have increased teachers’ accountability to effectively meet the needs of all students. This article draws upon recent empirical evidence on the impact of teacher-parent collaboration on inclusive education practices. It highlights some of the characteristics of an effective collaborative model and explores how far it contributes to a more inclusive classroom environment. The article also provides a contemporary insight into how teachers and parents view their collaborative roles in securing better student outcomes for students with special needs.